Sistemas agroflorestais urbanos: uma proposta de infraestrutura verde para uma urbanização agroecológica - D'Angelis, Gilberto Machel Veiga (2023)
The increase of green areas in cities brings numerous social, environmental, and economic benefits, both in its productive aspects (as in the movements of vegetable gardens and urban agriculture) and concerning the ecosystem services that can be added to the creation or expansion of urban forests (carbon sequestration, improvement of the microclimate, reduction of pollution, integration of people with the environment, leisure). However, a proposal aggregating all these benefits simultaneously, systemically, and integrated into the urban landscape is stillchallenging. Thus, based on the integrating concept of Continuous Productive Urban Landscapes (derived from architecture) combined with the concept of Urban Food Forestry, this research set out to investigate (through a broad critical review of the literature) the use of Agroforestry Systems (AFS) as a strategy to compose productive landscapes and integrate – at the same time – the promotion of numerous ecosystem services to the urban design of cities. The results indicate that Agroforestry Systems can be seen as a new and promising typology of Green Infrastructure (GI) to support projects of cities in transition to agroecological urbanization or to project cities of the future in which urban ecosystems are connected from the outset to natural ecosystems and can thus co-evolve and develop in a symbiotic and beneficial to the surrounding nature.